Wireless temperature monitoring and control - Mohd Faris, Ab. Abas (2009)
The goal of this project 1s to design a wireless temperature measurement and control using a Motorola 6&HC J1 microcontroller. The system is composed of to 2 main boards which is transmitting board and receiving board. The device performs the measurement of temperature by using sensor and transmit the measurement via wireless. The measured temperature will be displayed at Graphical User Interface (GUI) by connecting receiver board to the computer. The set point of the temperature will be compared with the measured temperature and when the set point is lower or higher, it will triggered the heater or cooler element The temperature will be measured and displayed continuously.